Meningkatan Motivasi Belajar Menggunakan Model Pembelajaran Picture And Picture pada Mata Pelajaran Ilmu Pengetahuan Alam - Laili Rahmi; Delya Yuswanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
Science learning that is not effectively by the teacher will affects the low learning motivation students. This is related to the results of observations at MIS Nailul Ikhsan Sungai Arang, Bungo city Jambi which students show are less active in learning and their lack of attention to teacher explanations. The measurement of initial motivation using the observation instrument of motivation also shows that the average percentage of achievement of the students' motivation indicators is only 39.8 which is in the